Development of Cultural Tourism Activities with the Participation of Khorum Local Community, Uttaradit Province - Rungsimuntuchat , Opal; Posrie, Tipaporn (Journal of Modern Learning Development, 2021)
The objectives of this research were 1. To study the status of tourism and local cultural tourism activities of Khorum, 2. Develop the cultural tourism activities by the participation of local communities of Khorum, and 3. The appropriate cultural tourism activities for the local community of Khorum. This study was qualitative and quantitative research with observation, Interview, questionnaires, group discussions. The qualitative case do divide into four area-participation groups of 35 people, including 1) Local administrators, 2) Entrepreneurs, 3) Community leaders, and 4) Community representatives. In quantity, Purposive Sampling. A questionnaire was collected from 307 people of 1,321 people and analyzed by statistical analysis and social science data synthesis. Study Results from 1. For the status, Khorum had outstanding cultural tourism resources. In history, Phraya Pichai Daap Hak. The community continues to form the Lao Wiang cultural way. Convenient transportation and have accommodation, but lack of management of tourist attractions and activities. 2. The development of cultural tourism activities with the participation of the local community Khorum found that the activities do divide into five aspects as follows; 1) Cultural and community-based tourism activities 2) Activity base ability to inherit wisdom and knowledge 3) Unique lifestyle activity base 4) the activity base on the continuity of culture and 5) the activity base on the local engagement with cultural attractions 3. An appropriate cultural tourism activity model of the local community found that four activities of suitable; as follows 1) Let Do It sculpture 2) Hab Jang Han Doll; Floating Sculptures 3) Travel activities of the Lao Vieng Buddhist Way and 4) Activity "Ton Peung," Bee Wax. There reflect the ability to inherit sustainable wisdom.